PENGARUH GOOD CORPORATE GOVERNANCE, MODAL INTELEKTUAL, DAN RASIO TERHADAP FINANCIAL DISTRESS - Stevani, Yosephine; Trisnawati, Ita; Supriatna, Dicky (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to obtain empirical evidence related to the components of good corporate governance, intellectual capital, and ratios that influence financial distress. This research uses a total of nine independent variables, namely institutional ownership, managerial ownership, independent commissioner, audit committee, sales growth, intellectual capital, operating capacity, working capital, and cash flow to sales. This research uses a sample of 231 data from 77 consumers non-cyclical and consumer cyclical companies that have been listed on the Indonesia Stock Exchange (BEI) during the period 2020 to 2022. This research uses a purposive sampling method in selecting samples and uses multiple regression analysis in data analysis. This research processes data with SPSS 25. The results of this research explain that the audit committee and operating capacity affect financial distress. The audit committee is tasked with protecting the interests of shareholders, in providing advice and recommendations in the company's financial and operational context, while operational capacity is used to measure its ability to manage assets in its operations. The more audit committees and the greater the operating capacity, the greater the potential for financial distress. Meanwhile, institutional ownership, managerial ownership, audit committee, sales growth, intellectual capital, working capital, and cash flow to sales do not affect financial distress.